Upaya Guru dalam Mengatasi Perbedaan Karakter Siswa di SDN 94 Pekanbaru - Risi, Habib Alpa; Pancasi, Lidiya; Nuraini, Risma Anandari; Mardianti, Vevi; Amelia, Yusfika; Mustika, Dea (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the issues faced by teachers in elementary schools, specifically at SDN 94 Pekanbaru. A qualitative method with an observational and interview approach was used with teachers and class supervisors. The results show that teachers provide new assignments after the previous ones are completed to keep students focused on learning. The main issue faced by teachers is the diverse student characteristics that require different approaches. Efforts made by teachers include guiding students, providing appreciation, and assisting students who face difficulties in learning. Active learning through discussions is also one of the solutions implemented by the teachers. Additionally, teachers use ice-breaking methods and visual media to address problems related to overly active or bored students. In conclusion, despite various challenges in teaching, the efforts made by teachers can enhance the effectiveness of learning at SDN 94 Pekanbaru.